2001
DOI: 10.1161/hc4501.098954
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Prediction of Ultimate Infarct Size at the Time of Acute Coronary Occlusion Based on the Extent and Magnitude of Collateral-Derived Myocardial Blood Flow

Abstract: Background We hypothesized that by detecting regions with adequate collateral-derived myocardial blood flow (MBF) within the risk area (RA), we could predict ultimate infarct size (IS) at the time of coronary occlusion. Methods and Results Group 1 dogs (n=15) underwent coronary occlusion without reperfusion, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
87
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 27 publications
(20 reference statements)
2
87
1
2
Order By: Relevance
“…12,13 MCE can also be used to define the extent of collateral perfusion during coronary occlusion and hence to predict the ultimate infarct size (provided mechanical intervention does not increase the infarct size from microembolism of atherosclerotic debris or from reperfusion injury). 14 The extent of collateral perfusion during coronary occlusion has been shown to correlate with the extent of viable myocardium. 15 The case discussed below illustrates an example of a patient with AMI who had extensive collateral flow.…”
Section: Acute Myocardial Infarctionmentioning
confidence: 99%
“…12,13 MCE can also be used to define the extent of collateral perfusion during coronary occlusion and hence to predict the ultimate infarct size (provided mechanical intervention does not increase the infarct size from microembolism of atherosclerotic debris or from reperfusion injury). 14 The extent of collateral perfusion during coronary occlusion has been shown to correlate with the extent of viable myocardium. 15 The case discussed below illustrates an example of a patient with AMI who had extensive collateral flow.…”
Section: Acute Myocardial Infarctionmentioning
confidence: 99%
“…Considering the ability of MCE for assessing microvascular integrity, this technique may be useful for quantifying myocardial viability after sucessful reperfusion in acute myocardial infarction [1] and to estimate infarct size [2]. To quantitatively analyse the different patterns of myocardial opacification following coronary occlusion and reperfusion, in this study, we propose a method that is able to aggregate information from myocardial contrast images and tissue characterization analyzes to compose a my ocardial perfus ion and texture polar map of the left ventricle in an animal model of myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…MCE can be used to reliably assess myocardial reperfusion following primary percutaneous coronary intervention (PCI) for AMI and to predict improvement in left ventricular (LV) function, as well as to assess the degree of collateral support to the infarcted territory (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) OBJECTIVES: To determine whether myocardial contrast echocardiography (MCE) can quickly and accurately assess myocardial perfusion and infarct-related artery (IRA) patency before emergency angiography during acute myocardial infarction (AMI). BACKGROUND: Despite encouraging experimental and clinical studies, the reliability and practicality of MCE in predicting IRA patency during AMI before angiography has not been proven.…”
mentioning
confidence: 99%
“…Thus, despite promising human and animal studies (14,(18)(19)(20)(21)(22), it remains to be shown whether the technique is practical and accurate in the clinical setting.…”
mentioning
confidence: 99%